PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATA PELAJARAN IPS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Zerri Rahman Hakim; M Taufik; Siti Mujiwati (Universitas Muhammadiyah Kuningan, 2019)
This study aims to determine the problem solving ability of learners using Problem Based Learning model (PBL) with learners using Direct learning model. The type of research used is quasi experiments in the form of non equivalent control group design, sampling is done by using purposive sampling technique. The selected sample is the IVA class as the treated experimental class and IVB as the untreated control class. Based on pretest data processing, the mean value of experimental class students is 29.5 while control class is 23.5. After learning, both classes are given posttest. Based on the data processing posttest obtained average results of problem solving ability of learners on subjects IPS experimental class of 69 while the control class 42.25 from the results of the difference test average. To test the hypothesis used inferential test. Based on the results of right-side test obtained t-count = 7.10 and t-table = 1.674. The result of this research can be concluded that the problem solving ability of students in IPS subject using Problem Based Learning (PBL) model is better than students using Direct Learning Model